E-029 Flow Diverter Treatment of a Ruptured Anterior Cerebral Artery Blister Aneurysm. (14th July 2013) - Toth, G; Bain, M; Hussain, S; Hui, F; Rasmussen, P
Abstract : Introduction: "Blister" type aneurysms (BA) are rare, atypical vascular lesions with fragile wall, broad base, difficult visualisation on imaging and high risk of rupture. Endovascular treatment of these aneurysms remains very challenging. While neck-remodelling with balloons and stents, or open surgery are available options, fragility of the thin aneurysm wall and lack of a true neck make treatment very high risk. The use of flow diverters is a possible alternative, but only limited data is available on this new therapeutic modality for BA treatment. Objective: We report a case of flow diverter placement allowing successful endovascular treatment of a ruptured "blister" aneurysm on the anterior cerebral artery (ACA). We review currently available literature on this topic. Methods: A 60-year-old female presented with extensive subarachnoid haemorrhage (SAH) from a left A1 segment 2.7 mm BA. An EVD was placed a day before intervention. The patient was loaded on aspirin and clopidogrel approximately 6 hours before the procedure. Adequate platelet response was confirmed by platelet aggregometry. Under general anaesthesia, a standard microcatheter and intermediate catheter were used to access the left ACA. The microcatheter was advanced into the left A2 segment, carefully passing the affected vessel portion and aneurysm neck. Slow deployment of the device was achieved without complications. A single device was used. For comparison and review, we searched the literature via standard online resources for flow diverter treatment of blister type aneurysms. Results: Successful placement of the flow diverter device resulted in excellent neck coverage and wall opposition. Immediate stagnation in the small aneurysm lumen was seen. Further follow-up angiograms at 3 and 7 days demonstrated complete occlusion of the aneurysm lumen. The patient's EVD was removed on postoperative day 7 while continuing antiplatelet agents without any complications. The patient made a good neurologic recovery. There are very few cases of ruptured BA flow diverter treatments currently published, none in smaller ACA vessels. Conclusion: We effectively treated an acutely ruptured BA in the ACA with a flow diverter device. Although peri-procedural management in the acute SAH period can be challenging due to the obligatory use of dual antiplatelet therapy, flow diverter treatment is now a potential therapeutic alternative for high-risk blister type aneurysms, even in smaller vessels. To our knowledge, this is the first report of a ruptured BA flow diverter treatment in ACA vessels. Disclosures: G. Toth: None. M. Bain: None. S. Hussain: None. F. Hui: None. P. Rasmussen: 1; C; ev3. 4; C; Penumbra, Blockade Medical. 6; C; ev3, Penumbra, Possis Medrad, Codman Neurovascular.